Perancangan Enterprise Arsitektur Menggunakan TOGAF ADM Di Bea Cukai Tanjung Pandan pada Aplikasi SIMPORA - Mohamad Firdaus (LPPM Universitas Nias Raya, 2024)
The web-based SIMPORA Customs Tanjung Pandan application is an efficient solution for optimizing annual budgeting business processes. Customers can easily get the latest information about the services provided in real-time. So it is hoped that it can improve performance significantly. To develop it, several data collection techniques were used, namely by conducting in-depth interviews, making observations and documenting them. Meanwhile, the research methodology is TOGAF ADM 9.1. This method is known to be the best method that can develop architecture in a structured and reliable manner. Several types of diagrams that help in designing this system are Value Chain, BPMN, Context Diagram, Use Case, and Class Diagram. It is hoped that this enterprise architecture design will enable budgeting to be monitored and improved immediately by stakeholders. The result of this research is an enterprise architecture design to support business processes at Tanjung Pandan Customs and Excise. It is hoped that various budgeting errors and design inaccuracies can be reduced and eliminated with this application, so that it can support the optimization of this institution's business processes.